2020
DOI: 10.1371/journal.pone.0231192
|View full text |Cite
|
Sign up to set email alerts
|

Topics and trends in artificial intelligence assisted human brain research

Abstract: Artificial intelligence (AI) assisted human brain research is a dynamic interdisciplinary field with great interest, rich literature, and huge diversity. The diversity in research topics and technologies keeps increasing along with the tremendous growth in application scope of AIassisted human brain research. A comprehensive understanding of this field is necessary to assess research efficacy, (re)allocate research resources, and conduct collaborations. This paper combines the structural topic modeling (STM) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 113 publications
0
18
0
Order By: Relevance
“…For quality assurance, the data retrieval was conducted in SCIE and SSCI databases, following previous review studies (e.g., [ 17 , 18 ]), because of the wide recognition of them [ 19 , 20 ]. At the prior stage of this study, we included book chapters, conference papers, non-SCIE and non-SSCI journal articles in the databases; after having read a few, however, we found problems of these papers and decided to exclude them.…”
Section: Methodsmentioning
confidence: 99%
“…For quality assurance, the data retrieval was conducted in SCIE and SSCI databases, following previous review studies (e.g., [ 17 , 18 ]), because of the wide recognition of them [ 19 , 20 ]. At the prior stage of this study, we included book chapters, conference papers, non-SCIE and non-SSCI journal articles in the databases; after having read a few, however, we found problems of these papers and decided to exclude them.…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric analysis is a method utilized in many fields to illustrate the landscape of subjects [12,13]. Based on CT, bibliometric analysis objectively includes articles of subject on subject in the analysis and reflects the evolution of a subject, trends of popular topics and collaborative relationships among researchers and countries [14][15][16]. To determine the influential research, the distribution of disparate topics and the evolution of research trends, we performed a bibliometric analysis of the top 100 most cited articles in clinical and experimental studies of DKD.…”
Section: Introductionmentioning
confidence: 99%
“…Such assessments are critical for prioritizing research and mobilizing resources for addressing research gaps in different branches of knowledge. Several bibliometric studies have shown the evolution of AI applications in different fields of health sciences [9,16,17]. Moreover, emerging bibliometric studies have reported how COVID-19 related research is increasingly produced globally [18][19][20].…”
Section: Introductionmentioning
confidence: 99%